Very sincerely yours - Winfrey, Kerry (Jove, 2021)
"A charming and heartwarming new romantic comedy by the acclaimed author of Waiting for Tom Hanks, Kerry Winfrey. Teddy Phillips never thought she would still be spending every day surrounded by toys at almost thirty years old. But working at a vintage toy store is pretty much all she has going on in her life after being unceremoniously dumped by her longtime boyfriend. The one joy that she has kept is her not-so-guilty pleasure: Everett's Place, a local children's show hosted by Everett St. James, a man whom Teddy finds very soothing . . . and, okay, cute. Teddy finds the courage to write to him, feeling slightly like one of the children who write to him on his show. He always gives sound advice and seems like he has everything figured out-and he pretty much does: Everett has a great support system, wonderful friends, and his dream job. But there is still that persistent feeling in the back of his mind that something is missing. When a woman named Theodora starts writing to Everett, he is drawn to her honesty and vulnerability. They continue writing to each other, all the while living their lives without meeting. When their worlds collide, however, they must both let go of their fears and figure out what they truly want-and if the future they want includes each other"--